IMPLEMENTASI DALAM PENYELESAIAN PERMASALAHAN AHLI WARIS PENGGANTI (STUDI BANDING BERDASARKAN HUKUM WARIS ISLAM DAN HUKUM WARIS PERDATA) - Sarijo Sarijo; Akhmad Khisni (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2017)
The study aims to determine the extent to which the replacement of substituted heirs in the case of a substituted heirs system, the implementation of substituted heirs and parts thereof, and the similarities and differences of substitute heirs under the Law of Inheritance and the Law of Inheritance of the Civil Code.The research used with approach method that is juridical normative method is legal research done by giving priority to researching library materials and documents. The specification in this research is using analytical descriptive, this method aims to provide an overview that is done by using a qualitative way that consists of: Theory-theory of law, legal doctrines, as well as opinions from legal experts.The results of this study and discussion: 1) The system of heirs according to Islamic Law is